PENGEMBANGAN APLIKASI EDUKASI KESEHATAN REPRODUKSI CALON PENGANTIN - Sri Mulyati; Ni Nyoman Sasnitiari; Risna Dewi Yanti; Fauzia Djamilus (Media Penelitian dan Pengembangan Kesehatan, 2025)
Marriage is an effort to get offspring and protect them to stay healthy both physically and spiritually. The Ministry of Religious Affairs has held a pre-marital guidance program for prospective brides, one of which is in the city of Bogor. One of the ministry of religion's programs is premarital guidance which is attended by 60% of prospective brides by 2022. The low participation of prospective brides in the pre-marital course is a serious problem that requires a solution. The purpose of the study was to determine the effect of android- based reproductive health education media on the knowledge of prospective brides in the Bogor City area. Research using the application development method was conducted from August to October 2024 in Bogor City. The research population was brides-to-be as many as 36 respondents, research informants, material experts and media experts. Data were collected through questionnaires. The results of the validation of the application material validator value 89% in the media aspect and 88% in the design aspect are categorized as very feasible to use. The results of the trial on bride-to-be respondents in the aspects of material suitability 100%, quality of learning design 86.1%, clarity of language use 88.9% and ease of installing the application 86.1%. the conclusion of the bride-to-be reproductive health education application is very feasible to use in increasing reproductive health knowledge. It is recommended that media applications can be developed for other health problems.